Theater - Burdick, Jacques. 4 0 16; 5 (New York : Newsweek Books, 1974)
Considers the rise of the theater from its origins in ancient Greece through Roman theater and the medieval plays which evolved in Europe, through England's great age of theater to present-day dramatic performances.
A chronology of theater: p. 178-184.;Includes index.
Bibliography: p. 185.
Young Adult;Young Adult.
Keywords: 2 -- 0; 6; History.;History. -- Theater;Theater; 20; 2